Fault monitoring and diagnosis of aerostat actuator based on PCA and state observer. (17th September 2019) - Zhang, Guochang; Chen, Li; Liang, Kuankuan
In order to solve the problem of actuator fault diagnosis for multi-propeller aerostats, this paper adopts the fault monitoring and diagnostic method that combines principal component analysis (PCA) and state observer. When the aerostat is running, the fault is detected in real time through the PCA method; once the fault occurs, the linearisation model of the system is obtained by the method of small disturbance linearisation and the failure factor of the fault is further calculated by the state observer. Therefore, the location and severity of the fault are obtained. The simulation results show that the fault diagnosis method based on the combination of principal component analysis and state observer can monitor and diagnose the failure of the aerostat actuator in real time.